If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2 + 3) + -2y = 3(4y + 3) Combine like terms: 2 + 3 = 5 4(5) + -2y = 3(4y + 3) Multiply 4 * 5 20 + -2y = 3(4y + 3) Reorder the terms: 20 + -2y = 3(3 + 4y) 20 + -2y = (3 * 3 + 4y * 3) 20 + -2y = (9 + 12y) Solving 20 + -2y = 9 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 20 + -2y + -12y = 9 + 12y + -12y Combine like terms: -2y + -12y = -14y 20 + -14y = 9 + 12y + -12y Combine like terms: 12y + -12y = 0 20 + -14y = 9 + 0 20 + -14y = 9 Add '-20' to each side of the equation. 20 + -20 + -14y = 9 + -20 Combine like terms: 20 + -20 = 0 0 + -14y = 9 + -20 -14y = 9 + -20 Combine like terms: 9 + -20 = -11 -14y = -11 Divide each side by '-14'. y = 0.7857142857 Simplifying y = 0.7857142857
| -14x^3+9x^2-2=0 | | 3/2x=189/20 | | -19x+4=0 | | 2(4w-1)=-10(w-3)+4 | | 5(x+5)=27 | | 30-5x=-5 | | 3.14*x^5-6x^4-9=0 | | pi*x^5-6x^4-9=0 | | 5x+5=137-6x | | 6x=121-5x | | 4x=63-5x | | 9(m-3)+3m=7m+43 | | 3.14x^5-6x^4-9=0 | | 12x-2=7x+23 | | 12x-2=7x+32 | | y=40ln(3x+8) | | 12-2u=8u+45 | | 124-3x=24+19 | | x/4+x+5/3=4 | | x-1/2x+x+3/4x=5/8 | | X^3-3x^2-x-3=0 | | 5/x+6=17/x | | x+2y+3z=1 | | 0.2y=3y | | 83-3x=10x+8 | | x=(8n+8n-1)2(4n-4n-1)2 | | 3p^4-8p^2+6=0 | | -5+11=14x-4-13x | | -15-(-31)=x/7 | | -6(t+1)=24 | | 20-14=3(x-2) | | b/7-18=-20 |